Short-term time-series observations of phytoplankton light-absorption and productivity in Prydz Bay, coastal Antarctica - Tripathy, Sarat C.; Kerkar, Anvita U.; Sabu, P.; Padhi, Sunil K.; Pandi, Sudarsana R.; Sarkar, Amit; Parli, Bhaskar V.; Mohan, Rahul (Frontiers in Marine Science, 2024)
The optical characteristics of coastal Antarctic waters exhibit complexity due to the dynamic hydrography influenced by meltwater intrusion, which alters nutrient levels, thermohaline structure, and optically active substances (OAS) regimes. Studies on bio-optical variability and its implications on phytoplankton productivity (PP) are scanty in coastal polar regions. On this backdrop, time-series measurements (72 h at 6 h intervals) of bio-optical properties such as phytoplankton biomass (chlorophyll-a), absorption (aph), and total suspended matter (TSM) concurrently with PP were measured to understand their interplay and variability in relation to the ambient physicochemical settings in the under-sampled Prydz Bay, coastal Antarctica. Our findings revealed thermohaline stratification within the bay, likely attributed to the inflow of less saline meltwater from nearby glaciers and minimal wind activity. The consistent presence of sub-surface chlorophyll maximum (SCM) beneath the stratified layer underscored the light-acclimatization response of shade-adapted phytoplankton. Surface waters exhibited higher TSM compared to deeper layers, indicating glacial melt influence, while the depth of the sunlit layer remained relatively stable, suggesting limited water mass movement and/or variability in OAS at the study site. An inverse relation between chlorophylla and chlorophyll-a-specific phytoplankton light absorption (a*ph(λ)) manifested 'pigment package effect' within the prevailing phytoplankton community, implying reduced lightabsorption efficiency and consequent lower PP. Compared to chlorophyll-a, the phytoplankton light absorption (aph(λ)) emerged as a better proxy for explaining PP variability. Nutrient availability was not limiting, which was conducive to micro (large) phytoplankton growth.Classification of phytoplankton size classes (micro, nano, and pico) based on the B/R ratio (aph at Blue (443 nm)/Red (676 nm) region) confirmed the dominance of larger (micro) phytoplankton that are more susceptible to package effect, thus have implications on reduced PP potential of this polar marine ecosystem.